Tracing the Evolution of Indian Detective Fiction (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Detective fiction is one of the genres that are deeply rooted in the literary tradition and presents a fascinating plot of evolution at the continental and cultural levels. In this paper, the historical background of Indian detective fiction is examined and traced up to the beginning of the 20th century, developing through various stages. Since the early works of Sharadindu Bandyopadhyay all the way to the modern dynamics influenced by the world, the development of the genre is studied in the context of the changes in the society, the evolution of the culture and the active nature of the change of the literature. The paper explores the multi-voicing of the story, the regionalism, the technological assimilation and how digital platforms have influenced the Indian detective fiction. Moreover, it also develops on the interaction of the British and Indian detective fiction and finds a curious crosspollination of cultural exchange, adaptation and evolution. Another important point of the narrative is that the female writers made tremendous contributions to the genre, offering new insights and breaking the traditions. In the process of passing through time, the interwoven history of British and Indian detective fiction stands out as an ode to the abundance of storytelling around the world.